1997
DOI: 10.1177/1087724x9700200105
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Planning in Large Urban Centers with Multiple Jurisdictions

Abstract: This article illustrates how a loss of municipal-levelplanning capability has occurred in metropolitan Miami, a large urban area with numerous independent municipalities. First, the loss of information bases crucial to decision making either because of exclusion or overload is described. Second, the impact of the loss or underuse of professional expertise in routine decision making is addressed. Third, solutions to the problem of inadequate municipal-level planning are discussed. In the course of proposing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is, of course, a strong theme in the closely-related field of regional planning. For example, Becker and Dluhy (1997) showed how loss of a regional planning capability in the Miami area, a large urban center with numerous independent municipalities, suffered with loss of planning data, loss of expertise and institutional memory, and in formulating solutions to shared problems. They suggested that since taxing authority will probably not be given to a regional planning authority, financing by contract will probably be required.…”
Section: Arrangements For Financial Responsibilitymentioning
confidence: 99%
“…This is, of course, a strong theme in the closely-related field of regional planning. For example, Becker and Dluhy (1997) showed how loss of a regional planning capability in the Miami area, a large urban center with numerous independent municipalities, suffered with loss of planning data, loss of expertise and institutional memory, and in formulating solutions to shared problems. They suggested that since taxing authority will probably not be given to a regional planning authority, financing by contract will probably be required.…”
Section: Arrangements For Financial Responsibilitymentioning
confidence: 99%